Organizational and Institutional Behavior in Pondok Pesantren with The Integrated Model - Dadan Sunandar; Abdul Rosyad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Today, there are many discourses related to the swift currents of change, pesantren still survive with the enthusiasm and high tradition/culture that is amazing. In the view of Muslims, it seems that Islamic boarding schools have been considered models of educational institutions that have advantages both from the aspect of the scientific tradition which is one of the great traditions, both in terms of transmission and internalization of the morality of Muslims. In this research, organizational behavior in Islamic boarding schools is based on the opinion of Colquitt, Lapine Weson, quoted by Siswoyo H & Halim P, that an integrative/combined model of organizational behavior was developed to improve three main goals including 1) organizational behavior; 2) individual performance; 3) Organizational commitment. Rist is through a literature study approach through various media related to "Organizational and institutional behavior in Islamic boarding schools with an integrative model". The pattern of behavior in Islamic boarding schools is essentially influenced by the effectiveness of the leadership of a kyai. Because the kyai is the highest leader in the pesantren organization. So this is illustrated in the kyai's efforts to always apply forms of Islamic boarding school organizational behavior, work ethics, spiritual intelligence, and an organizational commitment in Islamic boarding schools. In this case, a kyai is considered very special because there is an authoritative and admirable personality trait for anyone in the boarding school environment.